2014
DOI: 10.1111/1556-4029.12381
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Postmortem Redistribution of Fentanyl and Interlaboratory Variability,

Abstract: Fentanyl is a synthetic opioid agonist used for pain control. Often administered as a transdermal patch, it is an interesting drug for study of postmortem redistribution. We hypothesized that fentanyl concentrations would increase over time after death, as measured in blood drawn on the day prior to autopsy and in blood drawn at the time of autopsy in ten cases where fentanyl patches were identified at the scene. Concentrations were compared, and heart blood to femoral blood ratios were calculated as markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Carfentanil references: (Shanks and Behonick, 2017 ; Swanson et al, 2017 ; Hikin et al, 2018 ) . Fentanyl references: (Anderson and Muto, 2000 ; Kuhlman et al, 2003 ; Martin et al, 2006 ; Coopman et al, 2007 ; Biedrzycki et al, 2009 ; Carson et al, 2010 ; Krinsky et al, 2011 , 2014 ; Palamalai et al, 2013 ; Marinetti and Ehlers, 2014 ; McIntyre et al, 2014 ; Bakovic et al, 2015 ; Moore et al, 2015 ; Pearson et al, 2015 ; Poklis et al, 2015 ; Rodda et al, 2017 ; Dwyer et al, 2018 ) . Furanyl fentanyl references: (Mohr et al, 2016 ; Guerrieri et al, 2017a ; Martucci et al, 2017 ; Papsun et al, 2017 ) .…”
Section: Concentrations In Postmortem Specimens and Other Findingsmentioning
confidence: 99%
“…Carfentanil references: (Shanks and Behonick, 2017 ; Swanson et al, 2017 ; Hikin et al, 2018 ) . Fentanyl references: (Anderson and Muto, 2000 ; Kuhlman et al, 2003 ; Martin et al, 2006 ; Coopman et al, 2007 ; Biedrzycki et al, 2009 ; Carson et al, 2010 ; Krinsky et al, 2011 , 2014 ; Palamalai et al, 2013 ; Marinetti and Ehlers, 2014 ; McIntyre et al, 2014 ; Bakovic et al, 2015 ; Moore et al, 2015 ; Pearson et al, 2015 ; Poklis et al, 2015 ; Rodda et al, 2017 ; Dwyer et al, 2018 ) . Furanyl fentanyl references: (Mohr et al, 2016 ; Guerrieri et al, 2017a ; Martucci et al, 2017 ; Papsun et al, 2017 ) .…”
Section: Concentrations In Postmortem Specimens and Other Findingsmentioning
confidence: 99%
“…Krinsky et al. reported that the mean ratio of fentanyl concentration in peripheral blood samples drawn the day before autopsy and at the time of autopsy was 1.80 . However, in the Andresen et al.…”
Section: Resultsmentioning
confidence: 97%
“…Postmortem redistribution of fentanyl in the blood can occur (6,10,15,(23)(24)(25). Moore et al have reported that femoral blood concentrations taken 0.5 and 2 h after death increased from 1.6 to 14 ng/mL (15).…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach should be adopted in all cases of death from uncertain or questionable causes [ 66 , 70 ]. Past medical history and ante-mortem distribution, crime scene investigation, post-mortem toxicology examination, and toxicology findings should be carefully analyzed and considered on a case-by-case basis in light of all other data [ 11 , 98 , 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%